Reductive Fixation of Carbonate in Aqueous Solution by Nitrogen Plasma - Munegumi, T.; Harada, K. (Asian Journal of Chemistry, 2013)
A jet of nitrogen plasma blown into a sodium carbonate solution produced reductive fixation of carbonate to formate. The reaction is explained by the nitrogen-mediated oxidation-reduction of water.